2019
DOI: 10.3390/ijms20143545
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Organization of Repetitive DNA Elements and Extensive Karyotype Diversity of Silurid Catfishes (Teleostei: Siluriformes): A Comparative Cytogenetic Approach

Abstract: The catfish family Siluridae contains 107 described species distributed in Asia, but with some distributed in Europe. In this study, karyotypes and other chromosomal characteristics of 15 species from eight genera were examined using conventional and molecular cytogenetic protocols. Our results showed the diploid number (2n) to be highly divergent among species, ranging from 2n = 40 to 92, with the modal frequency comprising 56 to 64 chromosomes. Accordingly, the ratio of uni- and bi-armed chromosomes is also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 67 publications
1
17
0
Order By: Relevance
“…A similar distribution is also present in the chromosomes of the zebrafish, Danio rerio, showing (CA) n and (GT) n repeats clustered in the centromeric and telomeric regions (Shimoda et al, 1999;Supiwong et al, 2014) (CA) 15 and (GA) 15 , showed strong hybridization signals at subtelomeric and heterochromatic regions of several autosomes, in addition to a strong accumulation on the sex chromosomes (Cioffi et al, 2011, Supiwong et al, 2014. In fact, for most of these species, the 18S rDNA repeats are found in the short arms of a single chromosome pair (Ditcharoen et al, 2019), and this region matches the position of the (CGG)n marks found in our experiments. Similarities of both microsatellite and ribosomal DNA location do not seem to be a rare event among fishes, as they are also found in other species, such as Lebiasina bimaculata (Sassi et al, 2019) and Hepsetus odoe (Carvalho et al, 2017), for example.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A similar distribution is also present in the chromosomes of the zebrafish, Danio rerio, showing (CA) n and (GT) n repeats clustered in the centromeric and telomeric regions (Shimoda et al, 1999;Supiwong et al, 2014) (CA) 15 and (GA) 15 , showed strong hybridization signals at subtelomeric and heterochromatic regions of several autosomes, in addition to a strong accumulation on the sex chromosomes (Cioffi et al, 2011, Supiwong et al, 2014. In fact, for most of these species, the 18S rDNA repeats are found in the short arms of a single chromosome pair (Ditcharoen et al, 2019), and this region matches the position of the (CGG)n marks found in our experiments. Similarities of both microsatellite and ribosomal DNA location do not seem to be a rare event among fishes, as they are also found in other species, such as Lebiasina bimaculata (Sassi et al, 2019) and Hepsetus odoe (Carvalho et al, 2017), for example.…”
Section: Discussionmentioning
confidence: 99%
“…rDNA site is found in the telomeric region of the long arms of the 18 th chromosome pair (Ditcharoen et al, 2019), the same one that harbors a conspicuous (CAC)n site.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations